Robust palladium catalysts on nickel foam for highly efficient hydrogenations. Issue 23 (2nd November 2022) - Rahmani, Azina; Currie, Taylor M.; Shultz, Lorianne R.; Bryant, Jacob T.; Beazley, Melanie J.; Uribe-Romo, Fernando J.; Tetard, Laurene; Rudawski, Nicholas G.; Xie, Shaohua; Liu, Fudong; Wang, Ting-Hsuan; Ong, Tiow-Gan; et al.
Abstract : The combination of a polydopamine interface, solvothermal seeding of Pd(OAc)2, and ALD Al2 O3 overcoat enables the formation of evenly-coated, ultralow Pd loading Ni foam monolith materials. Abstract : The combination of a polydopamine interface, solvothermal seeding of Pd(OAc)2, and ALD Al2 O3 overcoat enables the formation of evenly-coated, ultralow Pd loading Ni foam monolith materials. The robust, easy to handle materials display excellent catalytic reactivity towards the hydrogenation of variably-functionalized nitroaromatics and styrenes at low temperatures and H2 pressure.